The Role And Authority Of Notary In Making A Financing Agreement In Sharia Banking - Razali Razali (Proceeding International Seminar of Islamic Studies, 2019)
Notary as a public official appointed by the government to assist the general public in making agreements that arise in the community. The role and authority of the Notary is related to the making of contracts relating to sharia banking, both financing contracts and other contracts which constitute sharia banking products. Sharia banking as a bank that uses sharia principles in conducting its business refers to the Alquran and Hadist. Sharia banks as financial intermediaries, namely collecting and distributing funds to the public with financing carried out in sharia principles. Financing agreements in sharia banking: murabahah financing contracts (financing the sale and purchase of goods with a profit), musyarakah (financing based on the principle of joint ventures), mudharabah (financing based on profit sharing principles), and ijarah financing contracts (financing of capital goods based on the leasing principle). The role and authority of a Notary in making a financing agreement in sharia banking is a general official authorized to make an authentic deed, concerning certain legal acts in particular, namely: murabahah, musyarakah, mudharabah and ijarah financing contracts. The notary official has the authority to make an authentic deed, especially the financing agreement in sharia banking. The role and authority of a Notary in making a financing agreement between an sharia bank and a customer is an authority arising from his position as a public official in Article 1 number (1) and Article 15 of Law No. 2/2014.